2013
DOI: 10.4236/ampc.2013.38046
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and Structural Investigation of Iron (III) Phosphate Glasses

Abstract: The regular melting-quenching method allowed isolating very large vitreous domains within the ternary system Li 2 O-P 2 O 5-Fe 2 O 3 at 1100˚C. The vitrification and crystallization effects are discussed in terms of phosphorus pentaoxide concentration (mol%). In the course of the present study, we analyzed chemical durability along the glass domain and many sample glasses were isolated. We noticed that our compounds demonstrated very high chemical resistance to attack, even with very highly concentrated minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…However, the possible existence of crystalline phases should not be excluded. 39,40 In agreement with the results of XRD, the FTIR measurements also do not indicate any type of modification in the glass matrix with the addition of silver. Figure 2 shows the FTIR spectra of all samples.…”
Section: Resultssupporting
confidence: 86%
“…However, the possible existence of crystalline phases should not be excluded. 39,40 In agreement with the results of XRD, the FTIR measurements also do not indicate any type of modification in the glass matrix with the addition of silver. Figure 2 shows the FTIR spectra of all samples.…”
Section: Resultssupporting
confidence: 86%
“…When the CaO content increases in the glass network, we see the disappear of the phase Ca 4 ) for x ≥ 25 mol%, which indicates the change of olygophosphate units in the form, presumably, of cyclic metaphosphate chains that result in agglomerates of crystallites amounting to a few tens of micrometres. These agglomerates lead to a clear improvement in chemical durability [14].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, phosphate glasses have lower glass transition temperature, higher thermal expansion coefficient and higher transmission in the UV region compared with silicate and borate glasses [2]. It is known that, phosphate glasses represent a dielectric energy-storage material, and therefore, they are useful for fabricating high energy density devices [3].The addition of transition metal oxides, such as Fe2O3, to phosphate glasses makes them more chemical resistive due to the replacing of the easily hydrated P-O-P bonds by the stronger Fe-O-P ones [4]. The effect of ZnO concentration on the dielectric properties of magnesium zinc phosphate glasses has been investigated [5], where the obtained results showed that the dielectric constant and dielectric strength rise with increasing ZnO content due to the increase of the dipole density associated to Zn 2+ ions.…”
Section: Introductionmentioning
confidence: 99%